Astrocyte-intrinsic regulation of central nervous system inflammation and neurodegeneration - Rothhammer, Veit; Quintana, Francisco J. (Clinical and Experimental Neuroimmunology, 2016)
Astrocytes constitute the majority of cells in the mammalian brain, where they carry out fine-tuned tasks that include, for example, the formation of the blood-brain barrier, the provision of structural support, the regulation of ion homeostasis and neurotransmitter recycling, and the modulation of neuronal function. In the context of autoimmune inflammation in the central nervous system during multiple sclerosis, these and other functions are challenged, while astrocytes modulate the local inflammatory response not only by regulating the blood-brain barrier permeability, but also by controlling the recruitment and activation of inflammatory cells and neurotoxicity. In the present review, we discuss astrocyte-intrinsic mechanisms that affect multiple sclerosis pathology and might provide potential targets for therapeutic intervention. Astrogliotic borders limit inflammatory lesion spread within the CNS. Scar formation around ongoing inflammation in the CNS is orchestrated by astrocytes, their endfeet, and the glial basement membrane, which form an astrogliotic scar and thus limit the uncontrolled perpetuation of the inflammatory lesion into unaffected areas of the CNS.
CRIS-Team Scopus Importer:2020-09-22
Keywords: astrocyte; multiple sclerosis; neurodegeneration; remyelination